Developing Social-Emotional Skills in Preschool Children Through Drawing and Storytelling Activities - Sudana, Ni Nyoman Tri Ayu Rupani; Ratih Andhini, Luh Putu; Widianti, Aritya (unprimdn.ac.id, 2025)
Preschool children are children aged 5 to 6 years who have various potentials. According to the World Health Organization's (WHO) 2019 report, 5-25% of preschool-aged children experience difficulties with their social-emotional skills, which have an impact on their readiness for school. Appropriate and engaging stimulation is crucial for supporting the social and emotional development of preschool children. Based on this background, this study aims to determine whether there are changes in the social-emotional abilities of preschool children before and after being given treatment in the form of drawing and storytelling activities. This study employed a quantitative experimental approach, utilizing a one-group pre-post test design. Data collection was conducted by involving raters who used observation sheets and documentation during the study. The participants in this study were 14 children from Group B at Taman Kanak-Kanak X, Mengwi District, Badung Regency. The results of this study showed that there were changes in the social-emotional abilities of preschool children before and after treatment in the form of an increase in several aspects of behavior through drawing and storytelling activities. This can occur because, during the activity, children have much interaction with their peers and can express the feelings or emotions they feel through the results of the drawing.